Relational Memory Expression Following Subliminal Presentations of Retrieval Cues - (:unkn) unknown (My University, 2014)
Questions about whether or not visual information can be processed in the absence of awareness have fostered substantial debate. Previous work has shown that eye movements are sensitive to memory for elements of prior experience, even in the absence of conscious awareness. By using subliminal memory cues, we were able to investigate whether or not eye movements are sensitive to memory for studied relationships when participants were unaware of the retrieval cues. The results indicated that more viewing was directed to faces that were studied with the subliminal scene cues but not selected relative to other non-selected faces during an implicit task. Also, the emergence of disproportionate viewing to the correctly identified scene associate was later than predicted for the control group during a subsequent explicit task. The results suggest that the effects of memory on eye movement behavior may occur in the absence of awareness of the retrieval cue.
Keywords: Eye Tracking; Implicit Memory; Relational Memory; Subliminal